The CO Quality Level Of Green Open Space (Case Study Of Jagakarsa District, South Jakarta) - Purnomosutji Dyah Prinajati (Journal of Natural Resources and Environmental Management, 2022)
Green Open Space serves indirectly to improve the level of public health. One of the sub-districts in South Jakarta is Jagakarsa is a potential area in the development of Green Open Space. Green plants as one of the elements of Green Open Space have the ability to reduce carbon and some air pollutants. Therefore, in this study an analysis of the relationship between Green Open Space in reducing carbon was carried out. Determination of the relationship between the area of Green Open Space and CO was carried out using the correlation analysis method. The results is proven that there is a very strong relationship between Green Open Space and CO with a correlation value of -0.865. Where every decrease in the existing area of Green Open Space (RTH) greatly affects CO levels.